The role of SPI1/VSIG4/THBS1 on glioblastoma progression through modulation of the PI3K/AKT pathway - Jie Shen; Lihui Zhou; Ke Ye; Jiangbiao Gong; Fan Wu; Kangnan Mo; Yu Zhu; Chao Chen; Renya Zhan (Journal of Advanced Research)
Introduction: Glioblastoma multiforme (GBM) poses a significant challenge in terms of treatment due to its high malignancy, necessitating the identification of additional molecular targets. VSIG4, an oncogenic gene participates in tumor growth and migration in various cancer types. Nevertheless, the precise process through which VSIG4 facilitates the malignant progression of glioma remains to be elucidated. Objectives: This research aims to explore the function and molecular mechanism involving VSIG4 in the malignant progression of glioma. Methods: The amount of VSIG4 was measured using qPCR, western blotting, and immunohistochemistry. Lentivirus infections were applied for upregulating or downregulating molecules within glioma cells. The incorporation of 5-ethynyl-20-deoxyuridine, Transwell, cell counting kit-8, and clone formation experiments, were applied to assess the biological functions of molecules on glioma cells. Dual luciferase reporter gene, RNA immunoprecipitation, and chromatin immunoprecipitation assays were used to explore the functional relationship among relevant molecules. Results: The upregulation of VSIG4 was observed in GBM tissues, indicating an adverse prognosis. Silencing VSIG4 in glioma cells resulted in a decrease in cell viability, invasion, proliferation, and tumorigenesis, an increase in cell apoptosis, and a stagnation in the cell cycle progression at the G0/G1 phase. Mechanistically, SPI1-mediated upregulation of VSIG4 expression led to binding between VSIG4 and THBS1 protein, ultimately facilitating the malignant progression of glioma cells through the activation of the PI3K/AKT pathway. The inhibited proliferative and invasive capabilities of glioma cells were reversed by overexpressing THBS1 following the knockdown of VSIG4. Conclusion: Our findings provide evidence for the role of VSIG4 as an oncogene and reveal the previously unidentified contribution of the SPI1/VSIG4/THBS1 axis in the malignant progression of glioma. This signaling cascade enhances tumor growth and invasion by modulating the PI3K/AKT pathway. VSIG4 as a potential biomarker may be a viable strategy in the development of tailored molecular therapies for GBM.